Enhancing the efficiency of laser-based powder bed fusion of metals through the use of localized and vertically directed shielding gas flow - Medvedev, Vadim; Kopp, Sebastian Paul; Roth, Stephan (Journal of Laser Applications, 2024)
The trajectory of metal additive manufacturing is transitioning from rapid prototyping toward on-demand and serial production. Consequently, the paramount objective remains the enhancement of additive manufacturing processes like laser-based powder bed fusion of metals (PBF-LB/M) to meet modern manufacturing needs and reduce environmental impact. Shielding gas flow significantly influences the mechanical properties in PBF-LB/M by protecting the metal from oxidation and removing process by-products from the powder melting zone. Accordingly, an improper shielding gas flow distribution can result in poor part quality, excessive inert gas consumption, and contamination of the building chamber. Presently, a lack of consensus remains regarding which configuration of shielding gas supply is the most appropriate in terms of process efficiency. This is the comprehensive investigation of a localized and vertically directed shielding gas flow and its effects on the properties of parts, also taking into account the reduction of inert gas consumption. In contrast to previous investigations, it is shown that enhanced surface roughness and relative density of the parts, as well as minimized contamination of the optics inside the building chamber is achieved through more efficient removal of metal plume particles from the processing zone by localized gas flow. Moreover, the developed computational fluid dynamics simulation model enabled the efficient determination of particularly promising gas flow configurations. Furthermore, the validation of the simulation model is demonstrated in an experimental environment. Finally, by localizing shielding gas flow, energy consumption can be reduced by almost half.
CRIS-Team Scopus Importer:2024-10-18
Keywords: additive manufacturing; laser-based powder bed fusion; process by-products; process efficiency; shielding gas flow